2018
DOI: 10.33687/ijae.006.02.2286
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood assessment of avocado growing in western Kenya and its socioeconomic implications using agricultural extension services

Abstract: Avocado (Persia americana) is an important world crop. In Kenya, it has become a very important crop but its production is limited by several factors. Studies were conducted in the Lake Victoria Basin counties of Bunyala in Busia, Kisumu, Muhoroni, Nyando and Rachuonyo in western Kenya to investigate the socioeconomic factors affecting Avocado production.  Information were collected from focus group discussions, key informants, individual interviews and secondary sources. Statistical Package for Social Scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Our results were however contray to the finding of Demie and Zeray (2015) who found that income from perennial crops was un-equally distributed. However, our results support the findings of George et al (2018) who showed that income from avocado production standardise household income and support livelihood. This implies that smallholder avocado producers earn good revenue from avocado production.…”
Section: Source Of Incomesupporting
confidence: 90%
See 1 more Smart Citation
“…Our results were however contray to the finding of Demie and Zeray (2015) who found that income from perennial crops was un-equally distributed. However, our results support the findings of George et al (2018) who showed that income from avocado production standardise household income and support livelihood. This implies that smallholder avocado producers earn good revenue from avocado production.…”
Section: Source Of Incomesupporting
confidence: 90%
“…) respecively. The results support the claim of George et al (2018) that the production of avocados can support and boost the livelihood of smallholder avocado producers. The results also reveal salary is the most income disparity with high relative conceetration (i.e.…”
Section: = −supporting
confidence: 83%
“…He noticed that there were no extension services to the surveyed avocado growing areas in the southwestern part of the country in 2006. The study by Gorge et al [57] reported that 50% of the 400 respondent avocado farmers in western Kenya never sought extension services due to some reasons including unavailability of extension agents, long distance to find extension services and not needing the services. Sotto [58] reported that extension services to Philippine avocado growers were poor due to lacking avocado technical knowledge by extension agents who were mainly deployed for staple food crops.…”
Section: Challenges Encountered By Smallholder Avocado Growers and Lomentioning
confidence: 99%
“…Soil and water are essential inputs to agricultural production [1], and in Nigeria, agricultural practice is crucial to the development and livelihoods of most of the population [2]. However, agricultural land use in Nigeria often results in the degradation of natural soil fertility and reduced productivity.…”
Section: Introductionmentioning
confidence: 99%